Challenges Encountered in the Compilation of an Advanced Shona Dictionary - Chitauro-Mawema, Moreblessings Busi (Lexikos, 2000)
Abstract: This paper highlights the challenges encountered by the African Languages Lexical (ALLEX) Project (at present the African Languages Research Institute (ALRI)) in Harare, Zimbabwe, which is in the process of compiling an advanced Shona dictionary (ASD). Its forerunner is the general Shona dictionary, Durarnazwi ReChishona (1996). The ASD is intended to be a comprehensive reference work, which will serve as a resource for more advanced users, especially those at higher secondary and tertiary education levels. The most important challenges have been in the areas of headword selection and the treatment of geographical/individual variation. The matters discussed here show the conflict between usage, i.e. popular acceptance, and (orthographic) norm, a problem often experienced in young literary languages subject to heavy foreign influence. This paper looks at: (a) the limitations of the current Shona orthography, the selection and codification of international vocabulary, and the presentation of variants and synonyms in the dictionary, and (b) the solutions suggested, and/or the ongoing debate on the topics. Keywords: HEADWORD, COMPILATION, DICTIONARY, GENERAL DICTIONARY, ADVANCED DICTIONARY, INTERNATIONAL VOCABULARY, VARIANT, VARIATION, SYNONYM, CROSS-REFERENCE, IMPLICIT CROSS-REFERENCE, EXPLICIT CROSS-REFERENCE Opsomming: Uitdagings teegekom in die samestelling van In gevorderdeSjona woordeboek. Hierdie referaat laat lig val op die uitdagings teegekom deur die AfricanLanguages Lexical (ALLEX) Project (tans die African Languages Research Institute (ALRI)) inHarare, Zimbabwe, wat besig is met die samestelling van ’n gevorderde Sjona woordeboek (ASD).Die voorloper daarvan is die algemene Sjona woordeboek Duramazwi ReChiShona (1996). Die ASDis bedoel om ’n omvattende naslaanwerk te wees wat as ’n hulpmiddel vir meer gevorderdegebruikers sal dien, veral di in die hoerskool of op universiteit. Die belangrikste uitdagings wasgelre in die lemmakeuse en die hantering van geografiese / individuele variasie. Die sake wat hierbespreek word toon die konflik tussen gebruik, d.w.s. populere aanvaarding, en (ortografiese)norm, ’n probleem wat dikwels voorkom in jong geskrewe tale onderworpe aan sterk vreemdeinvloed. Hierdie referaat beskou: (a) die beperkings van die huidige Sjona ortografie, die seleksieen kodifisering van die internasionale woordeskat, en die aanbieding van wisselvorme en sinoniemein die woordeboek, en (b) die voorgestelde oplossing en/of die voortgaande debat oor’hierdieonderwerpe. Sleutelwoorde: SOEKWOORD, KOMPILASIE, WOORDEBOEK, ALGEMENE WOORDEBOEK, GEVORDERDE WOORDEBOEK, INTERNASJONALE WOORDESKAT, VARIANT,VARIASIE, SINONIEM, KRUISVERWYSING, IMPUSIETE KRUISVERWYSING, EKSPLISIETEKRUISVERWYSING